Improving zinc accumulation in cereal endosperm using HvMTP1, a transition metal transporter. Issue 1 (9th June 2017) - Menguer, Paloma K.; Vincent, Thomas; Miller, Anthony J.; Brown, James K.M.; Vincze, Eva; Borg, Søren; Holm, Preben Bach; Sanders, Dale; Podar, Dorina
Summary: Zinc (Zn) is essential for all life forms, including humans. It is estimated that around two billion people are deficient in their Zn intake. Human dietary Zn intake relies heavily on plants, which in many developing countries consists mainly of cereals. The inner part of cereal grain, the endosperm, is the part that is eaten after milling but contains only a quarter of the total grain Zn. Here, we present results demonstrating that endosperm Zn content can be enhanced through expression of a transporter responsible for vacuolar Zn accumulation in cereals. The barley ( Hordeum vulgare ) vacuolar Zn transporter HvMTP1 was expressed under the control of the endosperm‐specific D‐hordein promoter. Transformed plants exhibited no significant change in growth but had higher total grain Zn concentration, as measured by ICP‐OES, compared to parental controls. Compared with Zn, transformants had smaller increases in concentrations of Cu and Mn but not Fe. Staining grain cross sections with the Zn‐specific stain DTZ revealed a significant enhancement of Zn accumulation in the endosperm of two of three transformed lines, a result confirmed by ICP‐OES in the endosperm of dissected grain. Synchrotron X‐ray fluorescence analysis of longitudinal grain sections demonstrated a redistribution of grain Zn from aleurone to endosperm. We argue that this proof‐of‐principle study provides the basis of a strategy for biofortification of cereal endosperm with Zn.